The Dangers of The Crime of Genocide: International Law Review - Dewa Gede Sudika Mangku; Kadek Astiti Narayani (Fakultas Hukum, Universitas Internasional Batam, 2022)
The crime of genocide in criminal law international law is an extraordinary crime and has become an prohibited which was later enshrined in the 1948 Genocide Convention, the statute International Criminal Tribunals for the Former Yugoslavia (ICTY), statute International Criminal Tribunals for Rwanda (ICTR) and the 1998 Rome Statute. This study aims to determine the crime of genocide that experienced when viewed in international law and dispute resolution methods genocide under international law. This research using normative doctrinal or juridical legal research. Research result states that the main cause of the crime of genocide is motivated by the struggle for the rights of ethnic minorities and the existence of fanatical and racial religions that are shown in discrimination cultural. Crimes committed by the Myanmar government by Ethnics Rohingya Muslims constitute an international crime of genocide, because has fulfilled several main elements, namely mass murder, discrimination against minority religions, is carried out systematically, and aims to eliminating certain ethnic groups and groups.